Blockchain and IoT Technology Transformation in Indonesian Education - Supriadi, Ajay; Iqbal, Muhammad Faiz; Pratista, Alva Nandana; Sriyono, Diaz Mauludin; Buanasari, Dheaka Jaya (Blockchain Frontier Technology, 2023)
Every area of life has been touched by technology, and the education industry is no different. Recently, there have been seismic shifts. Teachers and students used a blackboard technique in the traditional classroom teaching-learning process. But this process' characteristics have changed during the last few years. Technology has snuck in and significantly improved it. On the one hand, whereas in conventional classrooms the players were the teachers, the students, and the books, in the modern classroom the players are the teachers, the students, robots, the e-books, the laptops, and the books. With the help of e-lectures and tutorials, the teaching-learning process can now transcend geographical borders in classrooms. For the process, a vast amount of information is easily available. Additionally, the current situation shows a change from "Teacher-centered" to "Student Centric". However, the focus of this article is on utilizing the applications of Blockchain and IoT in the sector and identifying the areas where they prove to be advantageous. Several technologies have been major actors in modernizing the education industry. To comprehend and determine how these technologies offer a solution to significant educational difficulties, a thorough literature review must be conducted. The teaching and learning process needs to be understood in light of a variety of factors, including changes to the participants, the process itself, the results that are produced, and others. It is also necessary to identify the related difficulties. A thorough examination of these enables us to draw the conclusion that they can revolutionize education for the better in the future. Blockchain, in particular, is still relatively new, but because of the advantages it offers, further study and adoption will undoubtedly alter the teaching-learning process.